2021
DOI: 10.1177/1093526621998869
|View full text |Cite
|
Sign up to set email alerts
|

EWSR1-ATF1 Fusion in a Myoepithelial Carcinoma of Soft Tissue With Small Round Cell Morphology: A Potential Diagnostic Pitfall

Abstract: Myoepithelial tumors of soft tissue are rare mesenchymal neoplasms that overlap with their salivary gland and skin counterparts at both the histopathologic and molecular levels. EWSR1 gene rearrangements with various fusion partners represent a common genetic event in myoepithelial tumors of soft tissue, whether benign or malignant, and may prove useful as a diagnostic tool in difficult cases. However, the number of diagnostic entities with EWSR1 gene rearrangements has grown considerably in recent years, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The EWSR1 gene rearrangement has been documented in both these types of cancers. Leckey Jr. et al [ 16 ] reported a case of myoepithelial carcinoma of soft tissue with small round cell morphology having EWSR1-ATF1 gene fusion, but Skálová et al [ 17 ] found that clear cell myoepithelial carcinoma with EWSR1 gene rearrangement frequently involved PLAG1 gene fusions but no EWSR1 fusion transcripts, while EWSR1-ATF1 gene fusion has been observed in most cases of HCCC [ 18 ]. We used FISH detection on the EWSR1-ATF1 chimeric gene.…”
Section: Discussionmentioning
confidence: 99%
“…The EWSR1 gene rearrangement has been documented in both these types of cancers. Leckey Jr. et al [ 16 ] reported a case of myoepithelial carcinoma of soft tissue with small round cell morphology having EWSR1-ATF1 gene fusion, but Skálová et al [ 17 ] found that clear cell myoepithelial carcinoma with EWSR1 gene rearrangement frequently involved PLAG1 gene fusions but no EWSR1 fusion transcripts, while EWSR1-ATF1 gene fusion has been observed in most cases of HCCC [ 18 ]. We used FISH detection on the EWSR1-ATF1 chimeric gene.…”
Section: Discussionmentioning
confidence: 99%
“…These findings must strengthen or complement a conventional pathological diagnosis based on histological and immunohistochemical findings, anticipating further accumulation of the genetic and molecular findings. Concerning benign to malignant myoepitheliomas, EWSR1and FUS-related fusion genes with various partner genes have been detected [30][31][32][33]. In 2020, Suurmeijer, et al [17] reported that fusion genes involving EWSR1 and FUS were detected in 49 of 66 cases of benign to malignant myoepitheliomas.…”
Section: Discussionmentioning
confidence: 99%